2021
DOI: 10.7717/peerj.11781
|View full text |Cite
|
Sign up to set email alerts
|

Atlas of tissue-specific and tissue-preferential gene expression in ecologically and economically significant conifer Pinus sylvestris

Abstract: Despite their ecological and economical importance, conifers genomic resources are limited, mainly due to the large size and complexity of their genomes. Additionally, the available genomic resources lack complete structural and functional annotation. Transcriptomic resources have been commonly used to compensate for these deficiencies, though for most conifer species they are limited to a small number of tissues, or capture only a fraction of the genes present in the genome. Here we provide an atlas of gene e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 80 publications
(121 reference statements)
0
10
1
Order By: Relevance
“…For her study, she focused on the haploid conifer megagametophyte. While here results indicated that purifying selection is more effective in haploid tissue, she could not detect the expected reduced diversity of genes predominantly expressed in the megagametophyte (Cervantes et al 2021).…”
Section: Innovative Methods and Approachescontrasting
confidence: 80%
“…For her study, she focused on the haploid conifer megagametophyte. While here results indicated that purifying selection is more effective in haploid tissue, she could not detect the expected reduced diversity of genes predominantly expressed in the megagametophyte (Cervantes et al 2021).…”
Section: Innovative Methods and Approachescontrasting
confidence: 80%
“…To assess the influence of purifying selection on the nucleotide diversity of the tissue-specifically expressed genes we genotyped 20 megagametophytes from unrelated trees of a single population using exome capture (Kesälahti R. unpublished data). We identify tissue-specific genes based on a previousl study (Cervantes et al 2021). Analyses were done in six datasets, one for each tissue-specific set of genes, plus a dataset used as reference point which included all variable sites (hereafter refer as all-sites dataset).…”
Section: Resultsmentioning
confidence: 99%
“…For each gene, we obtained the tissue-specificity and gene expression level information across five tissues (megagametophyte, haploid, and four diploid tissues vegetative bud, embryo, needle, and phloem) from the TMM matrix reported in Cervantes et al 2021. We considered genes with a tau index score of 0.8 and up as tissue-specific (Yanai et al 2005).…”
Section: Identification Of Genes With Tissue-specific Expressionmentioning
confidence: 99%
“…We considered 1 349 291 SNPs obtained by mapping RNA‐seq reads to the Scots pine reference transcriptome ( https://www.ncbi.nlm.nih.gov/nuccore/GILO00000000.1 ). From this initial set, we first excluded markers identified in contigs associated with potential contaminants (fungi or microbes; Cervantes et al., 2021 ; Ojeda et al., 2019 ; https://figshare.com/articles/dataset/Pinus_sylvestris_assembly_Trinity_guided_gene_level_information/13109492/1 ). Second, we removed heterozygous SNPs in haploid samples.…”
Section: Methodsmentioning
confidence: 99%
“…For the UOULU RNA‐seq set, we provide information about the predicted multicopy status, orthologous genes identified in P . taeda (Zimin et al., 2014 ) and Pinus lambertiana (Stevens et al., 2016 ) based on BLASTN results (see details in Ojeda et al., 2019 ), and expression levels and tissue specificity in five tissues (Cervantes et al., 2021 ). This information is available in Data S1 .…”
Section: Methodsmentioning
confidence: 99%